Artistic means of expression in Goderdzo Chokheli’s story "Children of God" - Tsignadze, Shorena ("Intercultural Dialogues" Transactions, 2025)
The story portrays the events of the Second WW2 and the story of a soldier on the battlefield, who sends letters from the front line to his wounded friend, now returned to their village. The narrative employs a variety of artistic techniques that render it both emotionally resonant and intellectually engaging. Through the use of literary devices - particularly symbolism - Goderdzi Chokheli draws attention to fundamental aspects of Georgian identity, including the alphabet, faith, national consciousness, and moral integrity. Beyond the narrative itself lies the question of how the author communicates with and influences the reader. The impact of each word depends not only on its meaning but also on the deliberate precision with which it is chosen. A close analysis of the story reveals the linguistic tools that define its artistic expression, with symbolism standing out as the most prominent. Additionally, dialectal vocabulary appears frequently in the speech of the characters and occasionally in the narrator’s voice as well—for instance: "Did justice disappear from over the earth, you are going through in my pockets as I sleep it Well, look at me, from which side is it going to pass by me?" "We were young then, and young luck is its own young. Every day, when luck cries out, it seems that a youngsters needs luck just as much as an old man." Proverbs and folk expressions also feature prominently in the characters’ dialogue, adding cultural authenticity and thematic depth: "Whoever has time, drinks cold water"; "A worthless fly buzzes where lies lie"; "What am I doing is boiling my heart in the gloom of sorrow?" Chokheli frequently employs repetition to intensify emotional effect and reinforce key ideas: "I am never feared death and I am still not afraid of it"; "Look, giant, look, giant, how it has struck me!" "... God even knows that love is hidden in the heart of the heart, what love is in the heart of that love and what love is in the heart of that love"; "What is it like, are you a man or a giant ..." The story also makes extensive use of similes and metaphors, enriching the text with vivid imagery: "In the distant night, these trees light our way like candles"; "Angels were picking nuts as red as pomegranates and offering them to God"; "His angelic heart stopped beating, and Levan slept again." Ultimately, the diverse array of literary devices in the story serves as a spiritual compass, guiding the reader to reflect on enduring human values such as forgiveness, compassion, warmth, and faith.